PRAMUKA PEDULI BUMI: REHABILITASI LAHAN PERKEBUNAN TERDAMPAK BENCANA MELALUI PEMBERDAYAAN EKONOMI HIJAU MASYARAKAT NAGARI GUGUAK MALALO SUMATERA BARAT - SALMIYATI; Febrianti; Fadli Arsi (Awal Bros Journal of Community Development, 2026)
The Scouts Care for the Earth Program: Rehabilitation of Disaster-Affected Plantation Land through Green Economy–Based Community Empowerment in Nagari Guguak Malalo is a community service initiative aimed at restoring disaster-damaged plantation land while improving community welfare through sustainable natural resource management. The program was initiated due to land degradation, erosion, and low plantation productivity in several areas of Nagari Guguak Malalo, mainly caused by limited farmer knowledge and the inadequate application of appropriate cultivation technologies. The target partners are the Banda Pauah, Rawang Talao, and Suka Tani Farmer Groups, which have potential to develop plantation commodities but face constraints in sustainable land management. The program applied a participatory and collaborative approach involving students, farmer groups, local communities, and the village government in stages of problem identification, planning, implementation, and monitoring and evaluation. Key activities included land rehabilitation based on topographic conditions, construction of terraces and rorak for soil and water conservation, planting robusta coffee and avocado, application of appropriate cultivation technologies, and capacity-building through socialization, training, and mentoring for farmer groups. The results show the revitalization of approximately 2 hectares of robusta coffee plantations with about 1,200 seedlings planted and the development of about 1.3 hectares of avocado orchards with around 350 seedlings. The program improved farmer group managerial capacity, enhanced technical cultivation skills, and promoted environmentally friendly agricultural practices through conservation-based avocado orchard demonstration plots. The program contributes to plantation land rehabilitation, increased land productivity, and strengthened community empowerment through a sustainable local resource–based green economy approach.